2014
DOI: 10.3758/s13414-014-0747-7
|View full text |Cite
|
Sign up to set email alerts
|

Task specificity of attention training: the case of probability cuing

Abstract: Statistical regularities in our environment enhance perception and modulate the allocation of spatial attention. Surprisingly little is known about how learning-induced changes in spatial attention transfer across tasks. In this study, we investigated whether a spatial attentional bias learned in one task transfers to another. Most of the experiments began with a training phase in which a search target was more likely to be located in one quadrant of the screen than in the other quadrants. An attentional bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 68 publications
(105 reference statements)
8
48
1
Order By: Relevance
“…In the remaining study, they searched for the number 2 among 5s. The 2-among-5 task yielded similar RT and search slope as the T-among-L task (Jiang, Swallow, Won, Cistera, & Rosenbaum, 2015).…”
Section: Search Taskmentioning
confidence: 78%
See 1 more Smart Citation
“…In the remaining study, they searched for the number 2 among 5s. The 2-among-5 task yielded similar RT and search slope as the T-among-L task (Jiang, Swallow, Won, Cistera, & Rosenbaum, 2015).…”
Section: Search Taskmentioning
confidence: 78%
“…In all studies, (1) training was conducted under incidental learning conditions; (2) participants were healthy young adults; (3) viewpoint did not vary; (4) participants had unlimited search time; (5) the target was present on all trials; and (6) participants were tested without a working memory load. Most studies were previously published Jiang, Swallow, & Sun, 2014;Jiang & Swallow, 2013b, 2013aJiang, Swallow, Rosenbaum, & Herzig, 2013;Jiang, Swallow, et al, 2015;.…”
Section: Other Inclusion Criteriamentioning
confidence: 99%
“…Second, the small amount of money did not prevent reward-based effects from emerging in previous studies (Stankevich & Geng, 2014), and it was sufficient to drive goal-driven attention (Experiment 4). Finally, although reward-based attention was frequently assessed in transfer tasks (Anderson et al, 2011; Chelazzi et al, 2014), significant effects have been observed in the training task (Failing & Theeuwes, 2014; Jiang, Swallow, Won, Cistera, & Rosenbaum, 2014; Lee & Shomstein, 2014; Le Pelley et al, 2014). Thus, although it is important to explore effects of reward size and spatial precision in future research, we believe that alternative approaches are needed for a deeper understanding of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent results suggest that such transfer may not occur: a bias to attend to a region in space induced by probabilistic cuing did not transfer to a foraging task (Jiang et al, 2015). It is possible that spatial biases do not transfer because space must be shared for all manner of tasks (e.g., attending to the bottom right is relevant in typing, cooking, opening doors…).…”
Section: Introductionmentioning
confidence: 99%